Graft-versus-host disease: unexpected presentation with simultaneous hepatitis and pancreatitis. (2nd August 2016) - Fernandes, Samuel Raimundo; Alves, Antonio T; Cortes, Margarida Barreto; Cortez-Pinto, Helena
Abstract : We report the case of a 37-year-old man with a previous bone marrow transplantation presenting with abdominal pain, diarrhoea and jaundice. Laboratory evaluation showed marked elevated liver enzymes, amylase and lipase with ultrasonographic evidence of acute alithiasic pancreatitis. Liver biopsy was compatible with graft-versus-host disease and toxic hepatitis. The patient rapidly improved after increasing immunosuppression. Although gastrointestinal manifestations are common in graft-versus-host disease, clinical acute pancreatitis is rarely seen. Patients with graft versus host are seldom managed by gastroenterologists and hepatologists. An awareness of this condition is essential for the experienced clinician.